Tunable trap depth for persistent luminescence by cationic substitution in Pr3+:K1−xNaxNbO3 perovskites. Issue 5 (16th October 2018) - Li, Liyi; Castaing, Victor; Rytz, Daniel; Sontakke, Atul D.; Katayama, Yumiko; Tanabe, Setsuhisa; Peng, Mingying; Viana, Bruno
Abstract: The development of efficient red‐emitting persistent phosphor is still an ongoing challenge. In the search of persistent materials in red range, Pr 3+ is a good candidate owing to its transitions between 1 D2 and 3 H4 state at about 612 nm. In this paper, we investigated the red persistent properties of Pr 3+ ‐doped perovskite oxide ABO3, (A: K, Na and B: Nb), which can be elaborated as large single crystal. KNbO3 :Pr 3+ appears to have weak photoluminescence and no persistent luminescence. However, the cationic substituted compoundsK 1− x Na x NbO 3 :Pr 3+ ( x  = 0, 0.4, 0.5, 0.7 0.9, 1) exhibit intense persistent luminescence, which increases steadily with increase in Na content. We correlated persistence behavior with the position of Metal‐to‐Metal Charge Transfer (MMCT) band, which plays crucial role in tuning of the trap depth. The MMCT band position decreases with the addition of Na contents and the thermoluminescence peak shifts toward higher temperature indicating the formation of deeper traps. This is in good agreement with the enhancement of the persistent luminescence suggesting that a proper tailoring of MMCT is needed to design efficient Pr 3+ ‐persistent phosphors with better performance. A detailed analysis on the trap depth, bandgap energy, and persistent luminescence properties is reported tuning the composition in theK 1− x Na x NbO 3 :Pr powder. Abstract : Tunable traps depths are obtained by Na/K substitution. Electron and hole traps are evidenced by thermal analysis. This gives new insights in the persistent luminescence mechanism in the Pr3+− doped perovskite compounds.